Autonomous maneuver coordination via vehicular communication - Xu, Wenbo; Willecke, Alexander; Wegner, Martin; Wolf, Lars; Kapitza, Rüdiger (Proceedings - 49th Annual IEEE/IFIP International Conference on Dependable Systems and Networks Workshop, DSN-W 2019, 2019)
Autonomous vehicles can make local decisions based on the perception of their environments. However, individual decisions do not always result in the most efficient solution from a global point of view, because of a lack of coordination. To improve the traffic efficiency, multiple autonomous vehicles can be orchestrated in a spontaneous group. This is achieved by a recently proposed Maneuver Coordination service utilizing the vehicular communication. Vehicles equipped with the Maneuver Coordination service can share their planned driving trajectories with others close to them, detect potential conflicts and negotiate a new plan of trajectories. If the negotiation is successful, the vehicles can end up with a cooperative and more efficient joint plan, compared to the individual plans. In this work, we extend the Maneuver Coordination service by designing a coordination protocol for the negotiation. Our protocol can ensure an agreement and prevent conflicting maneuver changes. The negotiation procedure also takes potential network failures into account and keeps the impact of such failures at a relatively low level. We tested our approach on a V2X simulation framework. The evaluation results of a lane-join scenario show that the coordinated plan after negotiation has 50% less accumulated time loss compared to the default right-of-way rules.
CRIS-Team Scopus Importer:2022-07-19
Keywords: Autonomous Driving; Cooperative Driving; Vehicular Communication